Obesity and Sex Steroid Changes across Puberty: Evidence for Marked Hyperandrogenemia in Pre- and Early Pubertal Obese Girls - McCartney, Christopher R.; Blank, Susan K.; Prendergast, Kathleen A.; Chhabra, Sandhya; Eagleson, Christine A.; Helm, Kristin D.; Yoo, Richard; Chang, R. Jeffrey; Foster, Carol M.; Caprio, Sonia; Marshall, John C. (The journal of clinical endocrinology and metabolism, 2007)
Context: Peripubertal obesity is associated with abnormal sex steroid concentrations, but the timing of onset and degree of these abnormalities remain unclear. Objective: The objective of the study was to assess the degree of hyperandrogenemia across puberty in obese girls and assess overnight sex steroid changes in Tanner stage 1–3 girls. Design: This was a cross-sectional analysis. Setting: The study was conducted at general clinical research centers. Subjects: Thirty normal-weight (body mass index for age < 85%) and 74 obese (body mass index for age ≥ 95%) peripubertal girls. Intervention: Blood samples (circa 0500–0700 h) were taken while fasting. Samples from the preceding evening (circa 2300 h) were obtained in 23 Tanner 1–3 girls. Main Outcome Measures: Hormone concentrations stratified by Tanner stage were measured. Results: Compared with normal-weight girls, mean free testosterone (T) was elevated 2- to 9-fold across puberty in obese girls, whereas fasting insulin was 3-fold elevated in obese Tanner 1–3 girls (P < 0.05). Mean LH was lower in obese Tanner 1 and 2 girls (P < 0.05) but not in more mature girls. In a subgroup of normal-weight Tanner 1–3 girls (n = 17), mean progesterone (P) and T increased overnight 2.3- and 2.4-fold, respectively (P ≤ 0.001). In obese Tanner 1–3 girls (n = 6), evening P and T were elevated, and both tended to increase overnight [mean 1.4- and 1.6-fold, respectively (P = 0.06)]. Conclusions: Peripubertal obesity is associated with hyperandrogenemia and hyperinsulinemia throughout puberty, being especially marked shortly before and during early puberty. P and T concentrations in normal-weight Tanner 1–3 girls increase overnight, with similar but less evident changes in obese girls.